(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
In general, Crop production is concerned with monsoon adaptability. As a consequence, promoting different cultures involves operational risks. Natural disasters have the ability to impair agricultural production. Crop insurance is simply a method that may be used to protect against production risks in farming, and some preparation is needed to conceal any potential threats. The Indian government has tried with and worked on creating various crop insurances schemes to meet this requirement. The National Agricultural Insurance Corporation of India has been operating the National Agricultural Insurance Scheme (NAIS) since 2000. All of these suggestions, however, remained on paper, and the government’s crop insurance policy was not modified. The aim of this research study is to look at the growth and development of the national agricultural insurance system, as well as the key characteristics and advantages of NAIS. As a consequence, knowledge and proper implementation of the crop insurance system may assist Indian farmers to increase food output while reducing the risk of crop failure.